It's a Shit Show, and It's Fine: Symbolic Nonviolence Practices in Higher Education in 2020 - Evans, Aubree M. (Critical Education, 2023)
Through in-depth interviews with 22 university and college faculty who taught during COVID in 2020, this study examines symbolic violence and symbolic nonviolence in higher education using the post-qualitative method, thinking with theory. The concept of symbolic nonviolence, the intentional and systemic practice of recognizing and absorbing symbolic violence to transform the habitus, resulted from this study. During an inequitable pandemic which caused low grades, plagiarism, and exiting, faculty practiced three types of symbolic nonviolence: non-academic support, academic adjustment, and disciplinary superpowers, which increased communication and social support for students, provided services that institutions were unable to provide, remediated students academically, adjusted academic expectations to be more suitable to pandemic learning, and taught students how to transform the world using tools unique to their disciplines. Symbolic nonviolence practices have the potential to transform the reproduction of exclusionary practices in the institution of higher education, improving academic success and social mobility.